Colonialism, nominal socialism and social policies with a focus on civil servants in the Republic of Congo - Künzler, Daniel (Ревија за социјална политика/Journal of Social Policy, 2022)
This article, through an historical case study, addresses the forces driving social policies in the Republic of Congo. During the colonial period, formal sector employment was mainly limited to the colonial administration but was, nevertheless, comparatively large because many civil servants from French Equatorial Africa worked in the French Congo. They benefited from social policies such as family allowances, introduced earlier and set higher than in the rest of the federation. After Congo’s formal independence in 1960, the civil service benefited from regular wage increases and a separate pension scheme. The civil service was expanded disproportionately and became a pillar of power for the nominally socialist regime that took power in 1963. Initially, this could be financed by an oil bonanza, but during the 1980s and 1990s there was international pressure to reduce the civil servant payroll. The Labour Party government was better able to muddle through than the first multiparty government. Returning to power in 1997 after two periods of civil war, the post-socialist Labour Party did little to extend social policies to the population outside of the civil service. Health care fee exemptions were announced, but the law creating a universal health insurance fund in 2015 has not yet come into force, and the intended expansion of the Lisungi Cash Transfer Programme failed. Retired civil servants are clearly, still, a main focus of the rather limited policies. Frequent mentions in presidential speeches of salary catch-up and payment of pension arrears and their regular payment signals a continued willingness to support this critical group. This strategic preference, neither pro-poor nor progressive in any way, challenges the dominant focus on social policies in sub-Saharan Africa as donor-driven and concentrated on the informal sector.